Effects of dipyrone on the digestive tract - Collares,E.F. (2019)
Dipyrone (metamizole), acting through its main metabolites 4-methyl-amino-antipyrine and 4-amino-antipyrine, has established analgesic, antipyretic, and spasmolytic pharmacological effects, which are mediated by poorly known mechanisms. In rats, intravenously administered dipyrone delays gastric emptying (GE) of liquids with the participation of capsaicin-sensitive afferent fibers. This effect seems to be mediated by norepinephrine originating from the sympathetic nervous system but not from the superior celiac-mesenteric ganglion complex, which activates β2-adrenoceptors. In rats, in contrast to nonselective non-hormonal anti-inflammatory drugs, dipyrone protects the gastric mucosa attenuating the development of gastric ulcers induced by a number of agents. Clinically, it has been demonstrated that dipyrone is effective in the control of colic-like abdominal pain originating from the biliary and intestinal tracts. Since studies in humans and animals have demonstrated the presence of β2-adrenoceptors in biliary tract smooth muscle and β2-adrenoceptor activation has been shown to occur in dipyrone-induced delayed GE, it is likely that this kind of receptors may participate in the reduction of smooth muscle spasm of the sphincter of Oddi induced by dipyrone. There is no evidence that dipyrone may interfere with small bowel and colon motility, and the clinical results of its therapeutic use in intestinal colic appear to be due to its analgesic effect.